The effects of cervical cerclage on the vaginal microbiota and its metabolites in pregnant women - Zhang, Jun; Wang, Lihua; Zhang, Mengjun; Xu, Zhimin; Zheng, Yijing; Lv, Bingqing; Pan, Mian (Frontiers in Cellular and Infection Microbiology, 2025)
Cervical cerclage is widely used to reduce the risk of preterm birth in pregnant women. The effects of cervical cerclage on the vaginal microbiota and its metabolites are not fully clear. The purpose of this study was to explore the influence of cervical cerclage on the vaginal microbiota and its metabolites. Our results showed that the clinical characteristics [white blood cell (WBC), neutrophil, lymphocyte, monocytes, platelet, NLR, PLR, SII, SIRI, and C-reactive protein (CRP)] and α-diversity (Observed, Shannon, Chao1, and Simpson indexes) of the vaginal microbiota were not altered during pregnancy after cervical cerclage. 16S rRNA gene sequencing found that the relative abundance of Muribaculaceae and Blautia was significantly increased in the post-cerclage group compared with the pre-cerclage group, but the relative abundance of Sneathia was significantly reduced. In addition, the volcano plot revealed that a total of 19 metabolites [including alpha-hydroxyalprazolam, LPE (18:1(9Z)/0:0), PS(16:0/15:0), N-acetylhistamine, carnitine, pseudouridine, and allopregnanolone] were significantly changed during pregnancy after cervical cerclage. Pathway analysis based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database showed that the changes in the vaginal microbiota and its metabolites mainly involved purine metabolism and amino acid metabolism. The alteration in the vaginal microbiota and its metabolites induced by cervical cerclage is associated with the therapeutic efficacy of cervical cerclage. Further studies are needed to explore how the vaginal microbiota affects the outcomes of pregnancy.